The Influence of Herding Behavior and Anticipated Regret on Financial Literacy and Its Implications for Investment Decisions - Retha Tesalonika S.; Wirmie Eka Putra; Salman Jumaili (Accounting Profession Journal (APAJI), 2024)
In the context of investment decision-making, there are financial behaviors such as herding behavior and regret bias such as anticipated regret, and financial literacy skills that need to be considered. This research will look for the relationship of herding behavior and anticipated regret to financial literacy in providing implications for investment decisions. This research will use the Smart PLS 4 application tool, using Outer Model, Inner Model, and Hypothesis Testing with 44 Jambi University Capital Market Study Group students as the sample. The results showed that herding behavior affects investment decisions and financial literacy, anticipated regret affects investment decisions but has no effect on financial literacy, and financial literacy has no effect on investment decisions. Thus, the literacy skills possessed do not guarantee that in making investment decisions it goes according to the understanding of financial literacy possessed. The conclusion of this study is that financial literacy is unable to provide implications for herding behavior in making investment decisions and anticipated regret in making investment decisions.